2011
DOI: 10.1016/j.molcel.2011.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Interactions Select and Maintain a Specific Cell Fate

Abstract: The ability to specify and maintain discrete cell fates is essential for development. However, the dynamics underlying selection and stability of distinct cell types remains poorly understood. Here, we provide a quantitative single-cell analysis of commitment dynamics during the mating-mitosis switch in budding yeast. Commitment to division corresponds precisely to activating the G1 cyclin positive feedback loop in competition with the cyclin inhibitor Far1. Cyclin-dependent phosphorylation and inhibition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
197
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(217 citation statements)
references
References 57 publications
20
197
0
Order By: Relevance
“…Apparently, during the competition between the two groups of proteins, once one cell fate dominates, the proteins representing the other cell fate are suppressed completely. These results agree well with experimental data [13].We further investigate the relationship between the time of pheromone addition and Whi5P activation, as shown in Figure S3. Our calculation for the curve of cell fate decision indicates that there is a sharp transition point at 3 min (i.e., the critical addition time is 3 min.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Apparently, during the competition between the two groups of proteins, once one cell fate dominates, the proteins representing the other cell fate are suppressed completely. These results agree well with experimental data [13].We further investigate the relationship between the time of pheromone addition and Whi5P activation, as shown in Figure S3. Our calculation for the curve of cell fate decision indicates that there is a sharp transition point at 3 min (i.e., the critical addition time is 3 min.…”
supporting
confidence: 89%
“…The G1 checkpoint of a cycling cell is termed the Start point [17,18]. The mechanisms of feedforward regulation in cell fate decisionsPrevious studies have identified the fractions of Whi5 protein that are removed from the nucleus as the main indicator for the status of the G1 checkpoint trigger [13]. In the recent work of our group, the Start point is quantified mathematically by the largest derivative in the dose-response curve, which can be obtained from the relationship between the activation of Whi5 (i.e., the proportion of Whi5 that has been exported from the nucleus at 30 min) and the pheromone application time [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This structure clearly has many favourable dynamical features that we have documented in recent work in the yeast system: cell size control [16], positive feedback-driven coherent cell cycle entry [18,19] and irreversibility [20,44]. Many of these features have been attributed to the animal system as well [40,42].…”
Section: Were Rb E2f Kip1 Cyclins D and E Present In The Eukaryotimentioning
confidence: 62%
“…The transition point (i.e. Start) between these two steps corresponds to cell cycle commitment arising from the abrupt feedback-driven increase in G1 cyclin transcription rate [19,20].…”
Section: The G1 -S Regulatory Network In Budding Yeast and Animals Hamentioning
confidence: 99%